PELAKSANAAN KOORDINASI OLEH CAMAT DALAM PENYELENGGARAAN KETENTRAMAN DAN KETERTIBAN UMUM DI KECAMATAN TUAH MADANI TAHUN 2021-2022 - Gusri, Ahmad; ', Isril (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Government Regulation Number 17 of 2018 concerning Subdistricts in carrying out the duties of the Subdistrict Head in the Administration of Government where Article 10 point c states that the Subdistrict Head in leading the Subdistrict is tasked with coordinating efforts to maintain peace and public order. Coordinating the implementation of peace and public order includes responsibility, processes, regular arrangements, unity of action and coordination goals. The purpose of this research is to find out how coordination is carried out by the sub-district head in maintaining peace and public order in Tuah Madani District, as well as finding out what the inhibiting factors are in coordinating the implementation of peace and public order in Tuah Madani District in 2021-2022. This research uses qualitative methods, descriptive research type, conducted in Tuah Madani District, using primary data and secondary data, data collection techniques namely interviews and documentation. The results of the research show that the implementation of coordination carried out by the Tuah Madani sub-district head with the police, traffic division heads, religious leaders, RT/RW, and the community has been carried out but has not been optimal in discussing matters related to peace and public order. Factors that influence the implementation of coordination by the sub-district head regarding peace and public order are the lack of discussion regarding peace and public order in the Tuah Madani District work plan, and the lack of participation from the community in implementing the environmental security system (Siskamling) which should require an active role from all parties related to this matter. maintain peace and public order. Keywords : Coordination, peace, order